Efektifitas The 6 Steps Reasoning Diagnosis Method dan Intan,s Clinical Reasoning Model (ICRM) dalam Penentuan Standar Asuhan Keperawatan (SAK) pada Setting Keperawatan Maternitas - Lisa Suarni (Jurnal Kesehatan, 2017)
Nurses doing their task and function need to have a standard to be able to be controlled, to be paid, to be taught, to be applied, and to be a hospital legal decision, thus the arrangement of the standard should be adjusted according to patient and hospital condition. The nursing care standard arrangement with ISDA and ICRM approach will be tested in this study. This study aimed to identify nursing diagnosis with The 6 steps of diagnostic reasoning method, to identify NIC, NOC and to test effectivity of the arranged nursing care standard. Methods: Stage I: identify nursing diagnosis in the six most prevalent cases patients in the ward using the six steps. Stage II: according to the nursing diagnosis that has been identified researcher decides NIC choice using Intan’s Clinical Reasoning Model (ICRM), then selected NOC and NIC be tested its effectivity using t-test analysis. Stage I result shows that using the 6 steps of diagnostic reasoning method in section caesarean patients researcher identifies 13 diagnoses, 9 diagnoses in spontaneous birthing, 7 diagnoses in antepartum hemorrhage, 2 diagnoses in postpartum hemorrhage, 7 diagnoses in preeclampsia/ eclampsia, 4 diagnoses in early amniotic membrane rupture, 36 (94.4%) NOCs identification and 28 (93.3%) NICs are applicative. Meanwhile, on stage II which is to test the nursing care standard effectivity, 16 nursing care standard are effective with p-value<0.05.